Shanghai in transition : changing perspectives and social contours of a Chinese metropolis - Gamble, Jos, 1959- (RoutledgeCurzon, 2003)
In the decades following the introduction of Communist Party rule in Shanghai in 1949, the city's economy, infrastructure and links with the world all atrophied. However, the past decade has seen far-reaching economic reforms implemented to recreate Shanghai as a cosmopolitan, world financial and trade centre. This book focuses on the lives of local residents and their perceptions of their changing city, and presents an evocative series of ethnographic perspectives of the city's shifting sociological landscape in this period of transition.